Digyalipopeptide A, an antiparasitic cyclic peptide from the Ghanaian Bacillus sp. strain DE2B - Nartey, A.P.; Dofuor, A.K.; Owusu, K.B.A.; Camas, A.S.; Deng, H.; Jaspars, M.; Kyeremeh, K. (Beilstein Journal Organization Chemistry, 2023)
During the continued isolation of different bacteria from highly diverse, low human activity environments in Ghana and the subsequent characterization and biological activity studies of their secondary metabolites, we found both Gram-positive and Gram-negative Bacillus strains to be ubiquitous and widespread. One of such strains, the Ghanaian novel Bacillus sp. strain DE2B was isolat ed from rhizosphere soils collected from the Digya National Park in Ghana. Chromatographic purifications of the fermented cul ture extract of the strain DE2B, led to the isolation of a cyclic lipopeptide, digyalipopeptide A (1). Using 1D and 2D NMR data, mass spectrometry sequence tagging, advanced Marfey’s analysis, and the GNPS molecular networking we solved the full structure of digyalipopeptide A (1). We found that compound 1 is a member of a somewhat homologous series of peptides produced as a mixture by the strain containing the same amino acid sequence in the cyclic peptide backbone but differing only by the length of aliphatic fatty acid side chains. When tested against Trypanosoma brucei subsp. brucei strain GUTat 3.1 and Leishmania donovani (Laveran and Mesnil) Ross (D10), digyalipopeptide A (1) gave IC50 values of 12.89 µM (suramin IC50 0.96 µM) and 4.85 µM
Research Aricle
Keywords: Leishmania; lipopeptides; molecular networking